PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN UMUM POLI GIGI DI PUSKESMAS KAMPALA KABUPATEN SINJAI - Mutmainnah; Irmina Adi Ringrih; Ince Annisah Adawiyah Arifin (Institut Teknologi Kesehatan Dan Sains Wiyata Husada Samarinda, 2024)
The problem of dissatisfaction felt by patients often occurs in health service organizations, especially in community health centers. Public Health Center is the main level of service in the community. Kampala Health Center is the health center with the highest number of patient visits in 2022. There are complaints from patients regarding the services experienced at the Kampala Health Center dental clinic regarding service facilities, so researchers are interested in conducting research related to service quality on general patient satisfaction at the Kampala Public Health Center dental clinic. This study aims to determine the effect of service quality on general patient satisfaction at the Kampala Public Health Center dental clinic. This type of quantitative descriptive research with a research design using a cross sectional approach. The number of samples taken was 54 respondents using the purposive sampling method. Data collection uses a questionnaire. Data analysis uses univariate, bivariate, multivariate analysis or multiple linear regression. The results of simultaneous testing or F test showed that the significance value was 0.000, the coefficient of determination R2 was 0.681, and the t test or partial measurement obtained a calculated t value of reliability of 0.543, responsiveness of 2.454, assurance of -2.261, empathy of 0.967, and tangibility of 3.060. There is an Influence of Service Quality on General Patient Satisfaction at the Kampala Public Health Center Dental Clinic